Brain angiogenesis in developmental and pathological processes: regulation, molecular and cellular communication at the neurovascular interface - Lee, Hye Shin; Han, Jiyeon; Bai, Hyun-Jeong; Kim, Kyu-Won (The FEBS journal, 2009)
The vascular network of the brain is formed by the invasion of vascular sprouts from the pia mater toward the ventricles. Following angiogenesis of the primary vascular network, brain vessels experience a maturation process known as barriergenesis, in which the blood-brain barrier is formed. In this minireview, we discuss the processes of brain angiogenesis and barriergenesis, as well as the molecular and cellular mechanisms underlying brain vessel formation. At the molecular level, angiogenesis and barriergenesis occur via the coordinated action of oxygen-responsive molecules (e.g. hypoxia-inducible factor and Src-suppressed C kinase substrate/AKAP12) and soluble factors (e.g. vascular endothelial growth factor and angiopoietin-1), as well as axon guidance molecules and neurotrophic factors. At the cellular level, we focus on neurovascular cells, such as pericytes, astrocytes, vascular smooth muscle cells, neurons and brain macrophages. Each cell type plays a unique role, and works with other types to maintain environmental homeostasis and to respond to certain stimuli. Taken together, this minireview emphasizes the importance of the coordinated action of molecules and cells at the neurovascular interface, with regards to the regulation of angiogenesis and barriergenesis.